Gallbladder wall thickening in infectious mononucleosis: an ominous sign. Issue 847 (May 1996) - O'Donovan, N.; Fitzgerald, E.
Abstract : Gallbladder wall thickening (3 mm or greater) is a nonspecific finding with many causes. We describe two cases caused by infectious mononucleosis. Other causes of gallbladder wall thickening are described and the literature is reviewed. We suggest that the finding of gallbladder wall thickening in a patient with infectious mononucleosis implies that the patient is very ill, and its observation should lead to close patient monitoring.